(untitled) (Comillas Journal of International Relations, 2020)
The role of the cultural tradition of a nation manifested through its art works in international relations such as seen at the Universal Exhibitions during the second half of the 19th century has been documented, but it is particularly fascinating if we pay attention to Japan’s participation in such exhibitions. Japan understood this aspect of international politics explicitly and progressively configured its very own discourse on Japanese Art History, a subject which until that time had been primarily interpreted through Western perspectives. This article will try to analyze the different circumstances of Japan’s participation in these events, paying special attention to documents published or actions taken by Japanese authorities in order to disseminate knowledge of its heritage. While the improvement of material conditions in Japan had a direct influence in Japan’s representation in the exhibitions, already from the beginning there was a bet by the Japanese Government to be there. This indicates Japanese authorities’ priority to showcase Japan together with the rest of the participating nations in the hopes that Japan would be seen as one of the most developed nations. Another reason for such need to present itself to the world was the insistence by the rest of the developed countries on placing Japan within an inferior category, as less developed, and consequently, placing its art in the same inferior position. Within this evolution of Japan’s regaining its right to its own Art History, its participation in the Columbine Exhibition of Chicago in 1893 was epoch-making, since it was the first occasion in which the international public was presented with a consistent and solid discourse on Japanese Art History materialized in an architectonic pavilion considered to be one of the apexes of Japan’s artistic production. It was the first step into swinging the balance in the possession and articulation of knowledge on Japanese Art that would be completely secured by the time of the Paris Universal Exhibition of 1900.